Minimalist Approach for HoLEP with A Low-Power Holmium Source: A Retrospective Study - Inan, Ramazan; Buldu, Ibrahim (Urology Journal, 2025)
Purpose: To assess the efficacy and safety of very low-power Holmium Laser Enucleation of the Prostate (HoLEP) on a 30-W holmium laser source. Materials and Methods: With the approval of the local ethics committee, we retrospectively analysed 60 patients treated with HoLEP. There were 30 patients in the low-power (LP) group and 30 patients in the very low-power (VLP) group. For the LP group, we used a 60-W holmium laser machine. Throughout the en bloc process, we used laser settings of 2 J and 20 Hz. We used a 30-W low-power holmium source in the VLP group. We used laser settings of 2 J and 10 Hz. All patients were operated on by an experienced surgeon. We evaluated the surgical parameters and practicality of the low-power laser vs. the very low-power laser. Results: All patients underwent successful HoLEP in the very low-power group; it was not necessary to increase the output of the laser in any case. Mean preoperatively estimated prostate volume was 88.1 mL (range, 30-300 mL). Mean enucleation time and enucleation efficiency were 67.9 min (range, 25–150 min) and 0.99 gm/min (range, 0.8–1.8 gm/min), respectively. No patient required blood transfusion postoperatively. No stress urinary incontinence (SUI) was observed in the 3rd month postoperative follow-up. Conclusion: The use of a low-power laser source is encouraging for the learning curve of new surgeons who will begin HoLEP surgery; it can facilitate the adoption of HoLEP in developing countries, where the initial capital investment may be a major obstacle.